Institutional development of community forest management in Vietnam - CGIAR Research Program on Policies, Institutions, and Markets (2017)
ICRAF research contributed to the Vietnam Administration of Forestry (VNFOREST) in passing Decision 01/QD-TCLN-VP mandating the Forest Protection Department to oversee community forest management in the country.